Cost analysis of a humidification dehumidification desalination system with a packed bed dehumidifier. (1st September 2018) - He, W.F.; Wu, F.; Wen, T.; Kong, Y.P.; Han, D.
Highlights: Mathematical models of the HDH desalination system with packed bed dehumidifier is established. Thermodynamic performance of the HDH desalination system is obtained. Economic analysis of the proposed desalination system is completed. Influences from the effectiveness, top and ambient temperature on the economic performance of the HDH system are focused. Abstract: In this paper, a water-heated humidification dehumidification (HDH) desalination system, which is powered by the waste exhaust gas from a furnace, is applied to produce water. In order to overcome the corrosion from the seawater on the dehumidifier with a general heat exchanger, the packed bed is used to achieve the dehumidification process. Based on the mathematical models for the HDH desalination system, the relevant thermodynamic and economic performance are acquired. Furthermore, the influences from the effectiveness, top and ambient temperatures on the aforementioned performance are also investigated. The simulation results show that peak values of the water production and gained-output-ratio (GOR) are obtained as 84.60 kg h −1 and 1.44 at the balance condition of the dehumidifier. The total cost for all the heat and mass transfer areas rises from 470.81$ to 701.46$ when the mass flow rate of the dry air increases from 0.1 kg s −1 at to 0.5 kg s −1, while the unit cost of water production (UCWP) ascends from 6.20$ kg −1  h to 13.41$ kg −1  h. Furthermore, raising the effectiveness, reducing the spraying temperature into the humidifier is always effective to cut the unit cost of water production, while it is only useful within a limited range of air mass flow rate for a higher ambient temperature.